Predictability and pricing efficiency in forward and spot, developed and emerging currency markets. (October 2020) - Potì, Valerio; Levich, Richard; Conlon, Thomas
Highlights: Comprehensive study of the predictability of forward/spot exchange rates. We find excess-predictability of forward exchange rates for currencies of emerging economies. Excess-predictability is confined to portions of the sample period, especially the early one. We find much less excess-predictability of spot exchange rates than of forward ones The above is a manifestation of post-2008 persistent violations of covered interest parity. Abstract: We study the predictability of forward and spot exchange rates of currencies of emerging and developed economies from 1994 to 2016. Our purpose is to shed light on the efficiency of currency markets and how and why it has evolved over this time. For the currencies of emerging economies, our analysis of rates of return on forward contracts finds some evidence of excess-predictability, especially in the earlier parts of the sample period, consistent with the view that this portion of the foreign exchange market has only become efficient in recent times. When we turn our attention to excess-returns computed from spot exchange rates and spot interest rates, however, we find much less predictability. In particular, over our full sample period, we find no evidence of excess-predictability, in contrast with the results reported by Hsu et al. (2016) but in agreement with Kuang et al. (2014). The different predictability of spot excess-returns and rates of return on forward contracts is a manifestation of the widespread violation of covered interest parity which emerged with the onset of the 2008 financial crisis.